The Marketing Strategy of Jialyka Maharani Through Supporting Football Clubs in Facing the 2024 General Election - Kawwami, Afif Musthofa; Syukri, Ahmad; Syahfitri, Desta (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
Football holds significant popularity in Indonesia, particularly in Palembang, where it boasts a considerable fan base. This enthusiasm for football has not escaped the attention of Palembang's political sphere, with figures such as Jialyka Maharani, a member of the DPD RI of South Sumatra, actively engaging in supporting and showing concern for the city's 45 football clubs. This study investigates Jialyka Maharani's political marketing tactics, specifically her backing of football clubs, in preparation for the 2024 elections in Palembang City. The research adopts a theoretical framework rooted in marketing strategy and employs a qualitative research approach. Primary data is gathered through direct interviews. The findings reveal several elements of Maharani's marketing strategy: 1. Segmentation, targeting women and the younger demographic with similar characteristics or needs. 2. Targeting grassroots football clubs, totaling 45 in Palembang. 3. This positioning results in perceived assistance, providing costumes/jerseys and financial support to the involved clubs. 4. Push marketing, which involves direct engagement through attending meetings and club events. 5. Pass marketing, utilizing successful local teams and social media influencers. 6. Pull marketing, focusing on both conventional and social media channels, as well as a branded jersey associated with Jialyka Maharani.